(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
In the result of obligate parasitic fungi study in the territory of Nyzhniodnistrovskyi National Park (Odessa region, Ukraine) 57 species of the orders Albuginales (two species), Erysiphales (25), Peronosporales (3) and Pucciniales (27) were identified. 14 species are new for the territory of the Park. Rust fungus Puccinia arenariae is reported for the first time in the territory of Right Bank Steppe of Ukraine; species Erysiphe friesii, Golovinomyces macrocarpus, Phragmidium tuberculatum, Pseudoperonospora cubensis, Puccinia convolvuli and P. scirpi are rare for this region. Identified fungi parasitized on 61 species of host plants belonging to 53 genera and 26 families. Among these plants Myosoton aquaticum (Caryophyllaceae) is new for Ukraine host species of the rust fungus Puccinia arenariae.